Management of Pastures and Rangeland in Arid Western Rajasthan: A Review - Yadava, N D; Soni, M L; Rathore, V S; Bagdi, G L; V, Subulakhsmi; Gaur, Mahesh K (Annals of Arid Zone, 2019)
Ranges and pastures are the backbone of the arid zone animal rearing. Theclimatic adversities, fodder availability, large animal population in the region completelydepends on these pastures. Heavy grazing pressure, poor management and poor rainfallconditions are only responsible for poor yield and low carrying capacity (0.68 ACUha-1) of these ranges and grasslands. The restoration by reseeding and introduction ofperennial grasses, shrubs and bushes are the only option for increasing the productivity.Response to 20 kg N ha-1 application to grasses appeared to be favorable in arid regionshaving less than 300 mm rainfall. Growing trees such as Prosopis cineraria, Acacia niloticaand Zizyphus nummularia, and grasses Cenchrus ciliaris, C. setigerus, Dactylocteniumscindicum, Panicum antidotale, and Lasiurus scindicus together has also been a traditionalpractice in the Thar Desert. The agri-horti-silvicultural system having fruit trees + foddercrops + fast growing nitrogen fixers tree species providing good fodder for animals isanother option for increasing the intensity of crops and increase productivity per unitarea. Additionally, grazing management like rotational grazing is most important formaintaining the sustainable production.Key words: Range management, pastures, grass cover, grazing management